2007
DOI: 10.1111/j.1365-3059.2006.01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rhizoctonia solani from potato in Great Britain

Abstract: One hundred and thirty five isolates of Rhizoctonia solani were obtained from British potato crops between 2001 and 2003. Isolates were assigned to anastomosis group (AG) using conventional PCR assays for AG2-1 or AG3 or through the observation of hyphal interactions, where appropriate. A previously published primer set was modified in this study to enhance specificity for AG3PT. Most of the isolates (92·6%) belonged to AG3PT whilst some (6·7%) belonged to AG2-1. Only one isolate recovered (0·7%) belonged to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 35 publications
6
96
0
4
Order By: Relevance
“…Other studies have indicated that AG2-1 isolates from potato are generally not very virulent on potato plants (Carling andLeiner 1990a, Woodhall et al 2007), which was found also in this study. The black scurf symptoms caused by one Finnish AG2-1 isolate in one experiment were very mild, consistent with previous reports in which AG2-1 has been occasionally recovered from black scurf on tubers grown in the fi eld in Alaska (Carling and), Northern Ireland (Chand and Logan 1983) and the United Kingdom (Woodhall et al 2007).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Other studies have indicated that AG2-1 isolates from potato are generally not very virulent on potato plants (Carling andLeiner 1990a, Woodhall et al 2007), which was found also in this study. The black scurf symptoms caused by one Finnish AG2-1 isolate in one experiment were very mild, consistent with previous reports in which AG2-1 has been occasionally recovered from black scurf on tubers grown in the fi eld in Alaska (Carling and), Northern Ireland (Chand and Logan 1983) and the United Kingdom (Woodhall et al 2007).…”
Section: Resultssupporting
confidence: 78%
“…In the United Kingdom and France, 93 % and 94 % of the isolates of R. solani characterized from potato belonged to AG3, respectively. The remaining isolates were of AG2-1 or AG5 (Campion et al 2003, Woodhall et al 2007. Similar results indicating predominance of AG3 and occasional occurrence of other AGs have been reported from many other countries including Ireland (Chand and Logan 1983), Alaska ), Canada (Bains and Bisth 1995), USA (Bandy et al 1984(Bandy et al , 1988, Peru (Anquiz and Martin 1989), South Africa (Truter and Wehner 2004), China (Chang and Tu 1980), Japan (Abe and Tsuboki 1978), and Australia (Balali et al 1995).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Isolates belonging to other AGs (AG-2, AG-4, AG-5, AG-7, AG-8 and AG-9) are associated with potato diseases in different parts of the world, but cause little damage in comparison to AG-3 (Carling et al, 1987(Carling et al, , 1998Bains & Bisht, 1995;Woodhall et al, 2007).…”
Section: Anastomosis Groups Of Rhizoctonia Solanimentioning
confidence: 99%